Peningkatan Hasil Belajar Siswa dengan Menggunakan Alat Peraga IPA Kelas IV SD Muhammadiyah Sijabut - Nur Wahyuni; Jumiatik Jumiatik (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2025)
The low learning outcomes of class IV students at SD Muhammadiyah Sijabut are due to the lack of direct student involvement in the learning process. To overcome this problem, classroom action research (PTK) was carried out using science teaching aids. The aim of this research is to improve student learning outcomes by using class IV science teaching aids at SD Muhammadiyah Sijabut. The research subjects were 22 students, the research data sources were obtained from qualitative data in the form of data from observations of teacher and student activities as well as quantitative data in the form of test data on student learning outcomes. The results of the first cycle of research showed that 8 students out of 22 students completed individually with classical completeness of 36% and classical absorption of 63%. Meanwhile, the results of the second cycle of research experienced an increase with the number of students completing individually as many as 18 students out of 22 students who took part in learning with a classical completion percentage of 82% with a classical absorption capacity of 85%. Based on the results of this research, learning using science teaching aids can improve the learning outcomes of class IV students at SD Muhammadiyah Sijabut.